Women in Strengthening the Economy and Welfare of the Ummah in Maccini Sombala District, Makassar - Ismawati; Rosman, Romzie; Sulistyowati; Oktaviana, Ulfi Kartika; Hanifah, Nani; Sanurdi; Muhajir (Institute of Education and Social Research, 2024)
This research aims to educate women in Maccini Sombala Village about the role of women who are able to play a role in strengthening the economy and welfare of the community, as well as how to improve the economy according to sharia. This research is a type of qualitative and quantitative research (mix-methods). This research is a form of grounded research using the Participation Action Research (PAR) technique. Meanwhile, the quantitative method used in this research is the experimental method and data processing using the paired sample t test. The results of the research show that it plays a role in changing the views of women in Maccini Sombala District to take a broader view of the role of women, removing the limitations created by society regarding women's freedom of rights, as well as providing education regarding Islamic views and sharia financial management. There was also an increase in women's understanding in Maccini Sombala Village after the socialization activities were held.